The Southern Gas corridor and the US policy in the South Caucasus - Poghosyan, Benyamin (YSU Journal of International Affairs, 2022)
The article analyzes the US policy in the South Caucasus in the context of implementing the "Southern gas corridor" project. Since the collapse of the Soviet Union in 1991 the energy geopolitics has been one of the critical pillars shaping the US regional policy in the South Caucasus. The US strategic goal was to facilitate the transportation of Caspian oil and gas to the European markets circumventing Russia. The US played a vital role in fostering the construction of Baku - Tbilisi - Ceyhan oil and Baku - Tbilisi - Erzurum gas pipelines. Since the mid-2000s, the US has put significant efforts to launch the "Southern gas corridor," which envisaged the transportation of Azerbaijani gas to the European market through the Transanatolian and Trans-Adriatic gas pipelines. The southern gas corridor became operational in late December 2020 and would provide 10 billion cubic meters of gas to Italy, Bulgaria, and Greece annualy. Even though Azerbaijan does not possess sufficient gas reserves to challenge Gazprom positions in Europe, the US views the Southern gas corridor project as a significant contribution to the establishment of alternative energy transportation routes to Europe, perceiving this within the prism of evolving great power competition between the US, Russia, and China
Keywords: South Caucasus; Southern gas corridor; USA; EU; Azerbaijan; Armenia; Turkey; Russia; geopolitics; regional security; energy strategy